Decarbonization pathways of worldwide energy systems – Definition and modeling of archetypes. (1st March 2021) - Kueppers, Martin; Paredes Pineda, Stephany Nicole; Metzger, Michael; Huber, Matthias; Paulus, Simon; Heger, Hans Joerg; Niessen, Stefan
Highlights: Archetypes to summarize countries globally regarding their energy system. Framework to define, model and validate these archetypes. Archetype classification 44% better than simple geographic grouping. Photovoltaics and flexibility are identified and quantified as global challenges by the archetype modeling. Country modeling validates archetype approach with few outliers. Abstract: Energy system models help to find the optimal technology mixes for decarbonization strategies in countries worldwide. To reduce the modeling effort and analyze as many countries as possible, this paper proposes a novel approach of energy system archetypes which can be directly evaluated. These archetypes classify similar countries worldwide independently from their geographic location. Advantages of this idea are the setup of a transferable global database allowing for data reconstruction between countries, market size estimations, and the ability to compare peer countries facing similar challenges. To enable such modeling, a framework is developed in which the archetypes are defined, standardized modeling rules are developed, and the results are evaluated for validation. In a benchmark against simple geographic classifications, the presented clustering approach, which results in 15 archetypes, improves the variance between all countries and their corresponding archetypes by 44% compared to the variance between the countries and their geographic sub-regions. The model results of these archetypes state the need of balancing technologies for the daily cycle of photovoltaic generation and the general importance of flexibility in future decarbonized energy systems. Overall, the results confirm that archetypes are an adequate approach to derive the set of solutions for the decarbonization of worldwide countries.